2016
DOI: 10.15314/tjse.20098
|View full text |Cite
|
Sign up to set email alerts
|

Impact of plyometric training and weight training on vertical jumping ability

Abstract: The Purpose of the study was to find out the comparative effect of Plyometric and weight training on vertical jumping ability. For the present study 24 male students from Department of Physical Education, BHU Varanasi were selected randomly as the subjects for the study. The age of the subjects ranged between 18 -21 years. The variables selected for the present study were Plyometric and weight training (independent variable), vertical jumping ability (dependent variable). For the study pre test -post test rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…In our studies, the indicators of the development of speed-strength skills have been obtained that testify to the advisability of introducing a system of specially selected exercises into the training process of players. These results are confirmed by studies of Taskin, & Bicer (2015), Thakur, Mishra, & Rathore (2016) and Çñmenlñ, Koç, Çñmenlñ, & Kaçoğlu (2016), to develop appropriate training techniques for athletes. In addition, the level of development of explosive speed, speed endurance and strength affects on the intensity of the game activity of rugby players (Condello, et al, 2013).…”
Section: Discussionsupporting
confidence: 64%
“…In our studies, the indicators of the development of speed-strength skills have been obtained that testify to the advisability of introducing a system of specially selected exercises into the training process of players. These results are confirmed by studies of Taskin, & Bicer (2015), Thakur, Mishra, & Rathore (2016) and Çñmenlñ, Koç, Çñmenlñ, & Kaçoğlu (2016), to develop appropriate training techniques for athletes. In addition, the level of development of explosive speed, speed endurance and strength affects on the intensity of the game activity of rugby players (Condello, et al, 2013).…”
Section: Discussionsupporting
confidence: 64%
“…Various methods have been developed, especially to improve leg strength. Plyometric training is the most commonly used method [42]. When plyometric exercises are performed regularly and correctly, they contribute to performance improvement in sports (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Weight training has been shown to improve vertical jumping performance in most cases by 2-8 cm or 5-15% [22,23]. Exercises such as squats, lunges, leg presses, and toe raises with heavy loads (80-90% 1-RM) and low repetitions (4-6) are used to improve maximal strength [23,24]. Plyometric exercises, such as depth jumps, have also been shown to improve vertical jump performance [25].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the hamstringsto-quadriceps ratio (H/Q ratio) is related to variables that describe CMJ and DJ (drop jump) heights. A study found that the heights of CMJ and DJ were increased with higher H/Q ratios, indicating a positive relationship between muscle torque and vertical jump performance [24][25][26]. Another study evaluated the relationship between lower extremity strength, symmetry, and jump performance.…”
Section: Discussionmentioning
confidence: 99%